Tsetse immune system maturation requires the presence of obligate symbionts in larvae. - Brian L Weiss; Jingwen Wang; Serap Aksoy (PLoS Biology, 2011)
Beneficial microbial symbionts serve important functions within their hosts, including dietary supplementation and maintenance of immune system homeostasis. Little is known about the mechanisms that enable these bacteria to induce specific host phenotypes during development and into adulthood. Here we used the tsetse fly, Glossina morsitans, and its obligate mutualist, Wigglesworthia glossinidia, to investigate the co-evolutionary adaptations that influence the development of host physiological processes. Wigglesworthia is maternally transmitted to tsetse's intrauterine larvae through milk gland secretions. We can produce flies that lack Wigglesworthia (Gmm(Wgm-) yet retain their other symbiotic microbes. Such offspring give rise to adults that exhibit a largely normal phenotype, with the exception being that they are reproductively sterile. Our results indicate that when reared under normal environmental conditions Gmm(Wgm-) adults are also immuno-compromised and highly susceptible to hemocoelic E. coli infections while age-matched wild-type individuals are refractory. Adults that lack Wigglesworthia during larval development exhibit exceptionally compromised cellular and humoral immune responses following microbial challenge, including reduced expression of genes that encode antimicrobial peptides (cecropin and attacin), hemocyte-mediated processes (thioester-containing proteins 2 and 4 and prophenoloxidase), and signal-mediating molecules (inducible nitric oxide synthase). Furthermore, Gmm(Wgm-) adults harbor a reduced population of sessile and circulating hemocytes, a phenomenon that likely results from a significant decrease in larval expression of serpent and lozenge, both of which are associated with the process of early hemocyte differentiation. Our results demonstrate that Wigglesworthia must be present during the development of immature progeny in order for the immune system to function properly in adult tsetse. This phenomenon provides evidence of yet another important physiological adaptation that further anchors the obligate symbiosis between tsetse and Wigglesworthia.